Composição espacial da meiofauna bêntica da plataforma continental do Maranhão - AMORIM, Kerllon Rayanderson Kendrick Garcia (2022)
Meiofauna is classified as a group of organisms, which inhabit the interstices of sediments, from coastal regions to abyssal zones. The present study aims to describe a spatial composition of the benthic meiofauna on the Maranhão Continental Shelf (PC MA) in front of the Maranhense Gulf, in the rainy season and its possible correlations with environmental parameters. Sampling was carried out during the rainy season of April 2019, aboard the ship Ciências do Mar II, and 17 points were sampled, in two transects. Benthic meiofauna was extracted from the sediment by decanting and sieving (38µm). The environmental characterization revealed a shelf with homogeneous spatial variation, with a predominance of medium-sand sediments, and with the influence of three distinct water bodies: river water, coastal water and tropical water. A total of 21,073 individuals of benthic meiofauna were identified, distributed in 12 taxonomic groups, in addition to the nauplii of Copepoda. Among the main groups, Nematoda showed the highest abundance (56%), followed by Copepoda (18%). These two groups were classified as constant, being present in all samples, while Tanaidacea was the only group classified as rare. Biological indices indicate an unbalanced environment, with a low diversity index. An increase in the abundance of individuals was observed towards the edge of the shelf, so the depth may be the variable that best explained the distribution of meiofauna in PC MA